A Study of C^13 and C^14 Isoptope Effects Effects in Some Unidirectional Processes - Stevens, William (My University, 1952)
The c^13 isotope effect in acid and alkaline hydrolysis of both ethyl and tertiary butyl benzoate-carboxyl-c^14 have been measured. Significant isotope effects were found in all the hydrolyses except acid hydrolysis of the tertiary butyl oster. These results are additional evidence for the suggestion of Choen and Schneider that alkyl oxygen rather than normal acyl oxygen bond cleavage occurs when tertiary butyl benzoate is hydrolyzed in acid solution. No appreciable c^13 isotope effect was found to occur in thermal, aqueous, or acid-catalysed decarboxylation of anthranilic acid. From this observation and other experimental evidence, it is concluded that anthranilic acid decarboxylates by a bimolecular process in which the attack of the hydrogen ion is rate controlling. It is further suggested that the hydrogen ion attack is on the zwitterion at the c carbon position. Both the c^13 and the c^14 isotope effect in the decarboxylation of mesitoic acid were measured using a mass spectrometer. The c^14 isotope effect was found to be two and one half times the magnitude of the c^13 isotope effect instead of twice as present theory predicts.
Keywords: c^13; c^14; isotope effects; acid hydrolysis